The answer is B) which is letter E . hope this helps <3
The sequence: a 1 = - 4, a 2 = 8, a 3 = -16,...
a 2 = a 1 * r
8 = - 4 * r
r = 8 : ( - 4 )
r = - 2
a n = a 1 * r^(n-1)
a 5 = - 4 * ( - 2 ) ^4 = - 4 * 16 = - 64
Answer:
The fifth term in the sequence is - 64.
Answer:
Step-by-step explanation:
g(10) = (10^2-8)/(10+4)= (100 - 8)/14 = 92/14 = 48/7 or 6 6/7
To factor this fraction, you have be be aware of two special factoring formula:
a^3<span> + </span>b^3<span> = (</span>a<span> + </span>b)(a^2<span> – </span>ab<span> + </span>b^2<span>)
</span><span>(a+b)³ = a³ + 3a²b + 3ab² + b³
You can see the top part in this case is (x+y)^3, and the bottom (denominator) can be factor into (x+y)(x^2-xy+y^2)
we can cancel (x+y), so what we have left is (x+y)^2/(x^2-xy+y^2)
or (x^2+2xy+y^2)/(x^2-xy+y^2)
</span>
Answer:2/2/5
Step-by-step explanation:
If 3/4 = 9/5
what about 4/4
You get the answer as 12/5 which is 2/2/5
Hope this helped